Analysis of Possible Triggering Mechanisms of Severe Thunderstorms in the Tropical Central Andes of Peru, Mantaro Valley - Flores Rojas, José Luis (2019)
We acknowledge financial support from the International Foundation for Science, Sweden, Concejo Nacional de Ciencia y Tecnologia CONCYTEC, Peru, and the Wellcome Trust, U.K